SARS-CoV-2 lineages and naso-oropharyngeal bacterial communities in COVID-19 reinfection: A study in West Java, Indonesia - Sativa, Alvira R.; Asyifa, Isnaini Z.; Adzdzakiy, Muhammad M.; Iryanto, Syam B.; Nugroho, Herjuno A.; Wulandari, Ari S.; Yanthi, Nova D.; Nasrulloh, Mukh F.; Rahmawati, Ema; Alamanda, Cut NC.; Ristandi, Ryan B.; Rachman, Rifky W.; Robiani, Rini; Agustiyani, Dian F.; Wisnuwardhani, Popi H.; Wardiana, Andri; Ningrum, Ratih A.; Dharmayanthi, Anik B.; Prasetyoputri, Anggia; Fibriani, Azzania; Saputra, Sugiyono (Narra Sains Indonesia, 2025)
Continuous emergence of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants may influence viral transmission dynamics and alter interactions with the respiratory microbiota, potentially increasing the risks of reinfection. This study investigated cases of coronavirus disease 2019 (COVID-19) reinfection in West Java, Indonesia, with the aim of identifying the SARS-CoV-2 variants involved, characterizing their genomic mutations, and profiling the nasal and oropharyngeal microbiota associated with reinfection. Naso-oropharyngeal swab samples were collected from 42 COVID-19 reinfection cases and nine new infection cases. Whole genome sequencing was performed using Oxford Nanopore Technologies (ONT) MinION Mk1C and variant analysis was conducted using ARTIC workflow. Nexstrain and PANGOLIN were used to determine the lineages. Phylogenetic trees were constructed using IQ-tree and FigTree. Key mutations were identified by Cov-GLUE. Additionally, 16s rRNA amplicon sequencing was conducted on nine samples from each group to analyze bacterial communities using EPI2ME and MicrobiomeAnalyst. All identified SARS-CoV-2 strains in this study were Delta variant (B.1.617.2), predominantly lineage AY.23 (n=46, 90%), followed by AY.24 (n=3) and AY.109 (n=2). No differences in SARS-CoV-2 lineages were observed between reinfection and new infection cases. Unique hotspot mutations found only in COVID-19 reinfections included NSP3, V220A, S_T676I, ORF7a_V82A, and ORF7a_TI20I. Bacterial community analysis revealed no significant diversity differences (alpha and beta) between the two groups. While the most dominant phylum remained Terrabacteria in both groups, Streptococcus was dominant in COVID-19 reinfections, whereas Prevotella was dominant in new infection cases. Notably, Haemophilus parainfluenzae, Fusobacterium periodonticum, Fusobacterium nucleatum, and Leptotrichia buccalis had significant increases in reinfection cases. Despite the similarity in SARS-CoV-2 lineages causing both COVID-19 reinfection and new infection cases, the presence of distinct key mutations and bacterial species suggest their potential as biomarkers within this group.